Are Women in Science Less Ambitious than Men? Experimental Evidence on the Role of Gender and STEM in Promotion Applications - Müge Süer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
The gender wage gap is to a significant extent driven by gender-based job segregation. One of the potential culprits can be found in supply-side behavioral differences in promotion applications. In this study, using a controlled lab experiment, we disentangle the roles of gender, field of study, and task difficulty in promotion application decisions. Our study pro- vides three crucial findings. First, gender differences in self-limiting promotion application behavior are only present in STEM field students when exposed to a male task. Specifi- cally, when an easier alternative is available, women are less willing to apply for promotions concerning harder tasks than men. Second, there exists no significant difference between men's and women's willingness to apply for promotion concerning female jobs in STEM or non-STEM fields. Third, we find that previously reported gender differences in confidence are present only between STEM field students. The results also suggest that self-sorting into positions does not cause a decrease in overall welfare, however, it causes fewer promotions for women in STEM. We finally propose an easy-to-implement policy intervention to close the gender gap in STEM students when applying for a promotion.
Keywords: D91; J16; J62; C91; 330; gender differences; promotion application; self-limiting behavior; hierarchical segregation; STEM; male task; experiment